2007
DOI: 10.1016/j.exer.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic evidence for nuclear disulfide in isolated lenses of hyperbaric oxygen-treated guinea pigs

Abstract: Our laboratory treats guinea pigs with hyperbaric oxygen (HBO) as a model for investigating the formation of nuclear cataract. Previous analyses of lens supernatants using this model have shown an increase in disulfide (-SS-) and loss of sulfhydryl (-SH) in the lens nucleus of O 2 -treated animals. In this paper, we have used the non-invasive technique of Raman spectroscopy to confirm these findings in intact, freshly-excised lenses. Guinea pigs were treated 3 times per week with HBO for a total of 50 (4 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…gamma-glutamyl transpeptidase deficient mice develop nuclear opacities at 1 week secondary to cysteine deficiency [22], or that treatment with buthionine sulfoxide (BSO) results in lowered GSH levels and cataract in newborn rats [23] and very young mice [24] . Vice-versa, oxidative stress from hyperbaric oxygen duplicates many changes observed in the aging human lens [25]. Knocking out glutathione peroxidase (GPX-1) in mice leads to cataract formation [26], whereby changes in lens epithelial cell morphology and DNA breaks were also found under oxidant stress generated by either hydrogen peroxide (H 2 O 2 ) treatment or GPX-1 null condition [27].…”
Section: Discussionmentioning
confidence: 99%
“…gamma-glutamyl transpeptidase deficient mice develop nuclear opacities at 1 week secondary to cysteine deficiency [22], or that treatment with buthionine sulfoxide (BSO) results in lowered GSH levels and cataract in newborn rats [23] and very young mice [24] . Vice-versa, oxidative stress from hyperbaric oxygen duplicates many changes observed in the aging human lens [25]. Knocking out glutathione peroxidase (GPX-1) in mice leads to cataract formation [26], whereby changes in lens epithelial cell morphology and DNA breaks were also found under oxidant stress generated by either hydrogen peroxide (H 2 O 2 ) treatment or GPX-1 null condition [27].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these refractive changes regressed after the discontinuation of short-term therapy, suggesting that the increase in oxidation caused by hyperbaric oxygen is initially reversible. Subsequent studies in experimental animals confirmed the effect of high oxygen exposure on nuclear opacification and provided insight into some of the harmful effects of oxygen on the lens, including increased formation of protein-protein disulfide cross-links [57,[67][68][69][70] . These studies provide a direct link between excessive oxygen exposure and nuclear cataract.…”
Section: Oxidation and Nuclear Cataractsmentioning
confidence: 91%
“…14,15 Because of that there is growing interest in the use of Raman and SERS for the detection of biothiols and GSH in biological samples. Raman spectroscopy was employed to study the changes in the intensity of S-H and S-S bonds in the lenses of guinea pigs upon treatment 17 as well as for studying oxidative stress in trapped erythrocytes. 18 SERS has been previously employed for improving the sensitivity of Raman detection of GSH by relying on the bonding of the thiol group to Au or Ag nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%